Legal Awareness of Marital Rape A Comparison of Perspectives in Urban and Rural Areas - Normala; Setyobowo Sangalang, Rizki; Istani (Jurnal Ilmu Hukum Tambun Bungai, 2025)
Abstract: This research discusses the critical issue of marital rape in Indonesia, a form of sexual violence within households that persists despite being criminalised by the Domestic Violence Law (UU PKDRT) and the Sexual Violence Crimes Law (UU TPKS). The rising number of case reports indicates a gap between legal provisions and public perception, which is still influenced by social, cultural, and religious values. This study, which is, examines public legal awareness and the role of these values in viewing the criminalisation of marital rape, using a comparative approach between urban and rural areas. Using a juridical-empirical method, data was collected through questionnaires from 49 respondents in the city of Palangka Raya and several surrounding villages, then analysed using the approaches of legal positivism, legal realism, and natural law theory. The findings reveal a significant gap between the recognition of the term 'marital rape' and the understanding of its substantive legal aspects, particularly in rural areas. A strong patriarchal mindset was evident, with the majority of respondents rejecting bodily autonomy within marriage. Social values (57.1%) were identified as the primary influencing factor, surpassing religion (37.7%) and culture (6.1%). This study concludes that the mere presence of law is insufficient; a holistic approach that integrates massive education and cultural reconstruction is essential to align societal values with legal norms and ensure effective protection for victims. Keywords: Rape, Marriage, Criminalisation, Legal Awareness Abstrak Penelitian ini membahas mengenai isu kritis marital rape di Indonesia, yaitu bentuk kekerasan seksual dalam rumah tangga yang masih berlangsung meski telah dikriminalisasi oleh UU PKDRT dan UU TPKS. Meningkatnya laporan kasus menunjukkan kesenjangan antara ketentuan hukum dengan persepsi masyarakat yang masih dipengaruhi oleh nilai sosial, budaya dan agama. Studi ini menganalisis kesadaran hukum masyarakat dan peran nilai-nilai tersebut dalam memandang kriminalisasi marital rape secara komparatif di wilayah perkotaan dan pedesaan. Dengan metode yuridis-empiris, data dikumpulkan melalui kuesioner terhadap 49 responden di wilayah Kota Palangka Raya dan beberapa desa disekitarnya, lalu dianalisis dengan pendekatan teori positivisme hukum, realisme hukum, dan hukum alam. Temuan mengungkapkan kesenjangan besar antara pengenalan istilah marital rape dengan pehaman hukum substantif, khususnya di daerah pedesaan. Pola pikir patriarki yang kuat terlihat dari mayoritas responden yang menolak otonomi tubuh dalam perkawinan. Nilai sosial (57,1%) terindentifikasi sebagai faktor pengaruh utama, mengungguli agama (37,7%) dan budaya (6,1%). Studi ini menyimpulkan bahwa kehadiran hukum tidak cukup; diperlukan pendekatan holistik yang mengintegrasikan edukasi masif dan rekonstruksi budaya sangat penting untuk menyelaraskan nilai masyarakat dengan norma hukum dan menjamin perlindungan yang efektif bagi korban. Kata Kunci : Pemerkosaan, Perkawinan, Kriminalisasi, Kesadaran Hukum